Growth on Alpha-Ketoglutarate Increases Oxidative Stress Resistance in the Yeast Saccharomyces cerevisiae - Maria Bayliak; Nadia Burdyliuk; Volodymyr Lushchak (International Journal of Microbiology)
Alpha-ketoglutarate (AKG) is an important intermediate in cell metabolism, linking anabolic and catabolic processes. The effect of exogenous AKG on stress resistance in S. cerevisiae cells was studied. The growth on AKG increased resistance of yeast cells to stresses, but the effects depended on AKG concentration and type of stressor. Wild-type yeast cells grown on AKG were more resistant to hydrogen peroxide, menadione, and transition metal ions (Fe2+ and Cu2+) but not to ethanol and heat stress as compared with control ones. Deficiency in SODs or catalases abolished stress-protective effects of AKG. AKG-supplemented growth led to higher values of total metabolic activity, level of low-molecular mass thiols, and activities of catalase and glutathione reductase in wild-type cells compared with the control. The results suggest that exogenous AKG may enhance cell metabolism leading to induction of mild oxidative stress. It turn, it results in activation of antioxidant system that increases resistance of S. cerevisiae cells to H2O2 and other stresses. The presence of genes encoding SODs or catalases is required for the expression of protective effects of AKG.